Pemberdayaan Kader Posyandu Sebagai Upaya Pengendalian Stunting Berbasis Komunikasi Interpersonal dan Penguatan Ekonomi di Desa Sungai Tandipah [Empowering Posyandu Cadres as an Effort to Control Stunting Based on Interpersonal Communication and Economic Strengthening in Sungai Tandipah Village] - fajriannor TM, M; Fridolin, Agnes; Novianty, Nadya; Septia, Gusti Harifa; Aritonang, Shinta Nauli; Hikmah, Norul (Indonesia Berdaya, 2025)
Abstract. Stunting is a serious problem in Sungai Tandipah Village, Sungai Tabuk Subdistrict, Banjar Regency, with prevalence increasing from 11.9% (2022) to 18.42% (2024). Contributing factors include poor sanitation due to untreated river water consumption, low nutritional literacy, and vulnerable agricultural-based livelihoods affected by flooding. The partner in this program is Posyandu Mawar, with 10 active cadres whose roles in nutrition education, parenting, and stunting prevention remain suboptimal. The main issues are divided into social aspects—low communication skills among cadres, limited awareness of child nutrition among mothers, poor sanitation, and lack of educational media—and management aspects, such as weak financial management and underutilization of local food potential. Solutions offered include training in interpersonal communication, balanced nutrition, simple water filter development, educational toolkit creation, financial management training, and establishment of a mini nutrition stall based on local food. The program was implemented through five stages: socialization, training, technology application, mentoring, and sustainability planning. The results show increased cadre capacity, with 90% improving interpersonal communication skills, 100% understanding balanced nutrition principles, and 90% improving financial management knowledge. Tangible outputs include educational media, two prototypes of simple water filters, and a mini nutrition stall producing local food products, supporting sustainable stunting prevention in the community. Abstrak.  Stunting merupakan permasalahan serius di Desa Sungai Tandipah, Kecamatan Sungai Tabuk, Kabupaten Banjar, dengan prevalensi meningkat dari 11,9% (2022) menjadi 18,42% (2024). Faktor penyebab meliputi sanitasi buruk akibat penggunaan air sungai tanpa pengolahan, rendahnya literasi gizi, serta kondisi ekonomi berbasis pertanian yang rentan banjir. Mitra kegiatan adalah Posyandu Mawar dengan 10 kader aktif yang belum optimal dalam edukasi gizi, pola asuh, dan pencegahan stunting. Permasalahan utama mencakup aspek sosial, seperti keterampilan komunikasi kader yang rendah, minimnya kesadaran ibu balita, sanitasi yang buruk, dan ketiadaan media edukasi, serta aspek manajemen berupa lemahnya pengelolaan keuangan dan belum dimanfaatkannya pangan lokal. Solusi ditawarkan melalui pelatihan komunikasi interpersonal, gizi seimbang, pembuatan filter air sederhana, pengembangan toolkit edukasi, pelatihan manajemen keuangan, dan pembentukan warung gizi mini berbasis pangan lokal. Kegiatan dilaksanakan melalui lima tahapan: sosialisasi, pelatihan, penerapan teknologi, pendampingan, dan perencanaan keberlanjutan. Hasil menunjukkan peningkatan kapasitas kader, dengan 90% lebih terampil dalam komunikasi interpersonal, 100% memahami gizi seimbang, serta 90% lebih baik dalam manajemen keuangan. Produk nyata berupa media edukasi, dua prototipe filter air, dan warung gizi mini telah dihasilkan, mendukung keberlanjutan pencegahan stunting di masyarakat.